2014
DOI: 10.1111/tpj.12650
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis inositol pentakisphosphate 2‐kinase, AtIPK1, is required for growth and modulates phosphate homeostasis at the transcriptional level

Abstract: SUMMARYInositol hexakisphosphate (IP 6 ) provides a phosphorous reservoir in plant seeds; in addition, along with its biosynthesis intermediates and derivatives, IP 6 also plays important roles in diverse developmental and physiological processes. Disruption of the Arabidopsis inositol pentakisphosphate 2-kinase coding gene AtIPK1 was previously shown to reduce IP 6 content in vegetative tissues and affect phosphate (Pi) sensing. Here we show that AtIPK1 is required for sustaining plant growth, as null mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(131 citation statements)
references
References 88 publications
8
123
0
Order By: Relevance
“…The ipk1-1 mutant deficient in InsP6 synthesis also is affected in the Pi signaling cascade (Stevensons-Paulik et al, 2005;Kuo et al, 2014). It is thus possible that Pi deficiency influences both Pi and JA signaling pathways via the modulation of the inositol polyphosphate pool.…”
Section: Discussionmentioning
confidence: 99%
“…The ipk1-1 mutant deficient in InsP6 synthesis also is affected in the Pi signaling cascade (Stevensons-Paulik et al, 2005;Kuo et al, 2014). It is thus possible that Pi deficiency influences both Pi and JA signaling pathways via the modulation of the inositol polyphosphate pool.…”
Section: Discussionmentioning
confidence: 99%
“…Since H3K4me3 is thought to be a binding platform for transcriptional activators and for factors that mediate transcript elongation and mRNA maturation, the authors suggested that AL6 could affect transcript maturation and stability of critical genes involved in root hair elongation [28,29]. A recent study from the same group revealed that histone acetylation was involved in Pi homeostasis, through the investigation of the Arabidopsis histone 2 Cell signalling and gene regulation H2A.Z P IPK1 Involved in the transcriptional regulation of some Pi starvationresponsive genes [38] deacetylase 19 (HD19) [31]. Indeed, characterization of the Arabidopsis HD19 mutant and over-expressing plants revealed a key role of HD19 in controlling root cell elongation in both Pi deficient and sufficient conditions as well as being involved in regulating a subset of key phosphate starvation induced genes, including some of the SPX genes involved in Pi sensing and signalling [31].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…The involvement of H2A.Z in regulating Pi homeostasis in plants has recently been strengthened through the study of the role of the Arabidopsis inositol pentakisphosphate 2-kinase coding gene (AtIPK1) that is involved in the biosynthesis of phytic acid, the main source of P in the seed [38]. Indeed, mutation of IPK1 resulted in numerous phosphate starvation-induced genes being induced, and correlated with a reduction of histone variant H2A.Z occupation in the chromatin at these loci [38].…”
Section: Histone Variantsmentioning
confidence: 99%
“…Inositol polyphosphates regulate critical cellular functions in eukaryotic cells (Munnik and Nielsen, 2011;Munnik and Vermeer, 2010;Gillaspy, 2013;Tsui and York, 2010;Kuo et al, 2014;Lee et al, 2015), and the discovery that these molecules bind to plant hormone receptors provides an interesting case model to study plant hormone perception. For instance, the ASK1-TIR1 component of the auxin receptor complex was copurified and cocrystallized with insect cellderived inositol hexakisphosphate (InsP 6 ; Tan et al, 2007).…”
mentioning
confidence: 99%